A Near Lossless Multispectral Image Compression using 3D-DWT with application to LANDSAT Images - Kalavathi, P; Boopathiraja, S (International Journal of Computer Sciences and Engineering, 2025)
Image compression is a technique which reduces the storage requirements of an actual image with fewer bits. Especially, the high dimensional images need a lot because of the exponential rate of its contained information. As multispectral images are represented in the form of different bands, it is three-dimensional in nature and demands larger memory spaces. There are several lossy and lossless compression methods are available for these types of images and the lossless one is more preferable. But, the problem is that the lossless methods on multispectral images yields better quality images but lack in the compression performance. Hence, there is need for optimal compression method that incorporate both the quality and compression performance. In this paper, we proposed a near lossless compression method for multispectral images. Three-Dimensional Discrete Wavelet Transform is used for decomposition and the Huffman coding followed by thresholding is used for encoding. The results of our proposed method for the multispectral LANDSAT images are discussed and compared with other existing methods in terms of PSNR and SSIM